Implementation of a framework for graph-based keyword search over relational data. (12th January 2023) - Cozza, Vittoria
The challenge of easily interconnecting and exploiting the increasing amount of data from structured data sources is still a primary concern for researchers from the industry and the academy. Keyword search over structured data systems (KSS) has attracted much interest as it provides a simple interface to query structured data. At the best of our knowledge, KSS evolved neither into a standard model nor into a commercial product. The implementation of every new system published so far was isolated from the previous systems, even when it advanced the state of the art for a single aspect. Also, the source code of these systems is not shared and the experimental results are not easily replicable. The present study aims at filling this gap, by the design and the shared implementation of a unified framework for graph-based KSS.